Metal Poisoning: Threat and Management - SJS Flora (Al Ameen Medical College, 2009)
Exposure to toxic metals remains a wide spread occupational and environmental problems in world. Due to their widespread use in human activities such as industry, agriculture and even as medicine numerous health risks may be associated with exposure to these substances. Lead, arsenic and cadmium generally interferes with a number of body functions such as the haematopoietic system, central nervous system (CNS), liver and kidneys. Over the past few decades there have been growing awareness and concern that the toxic biochemical and functional effects are occurring at lower level of metal exposure than those that produce overt clinical and pathological signs and symptoms. Despite many years of research we are still far from an effective treatment of chronic heavy metal poisoning. The main therapeutic option for chronic metal poisoning relies in chelation therapy. Chelating agents are capable of linking together metal ions to form complex structures which can be easily excreted from the body. They have been used clinically as antidotes for acute and chronic poisoning. 2, 3-dimercaprol (BAL) has long been the mainstay of chelation therapy of lead or arsenic poisoning. Meso 2, 3, -dimercaptosuccinic acid (DMSA) has been tried successfully in animals as well as in few cases of human lead or arsenic poisoning. However, one of the major disadvantages of chelation with DMSA has been its inability to remove heavy metal from the intracellular sites because of its lipophobic nature. Further, it does not provide protection in terms of clinical/ biochemical recovery. A new trend in chelation therapy has emerged to use combined treatment. This includes use of structurally different chelating agents or a combination of an antioxidant and a chelator to provide better clinical/biochemical recovery in addition to mobilization of heavy metal form intracellular sites. The present review article attempts to provide update information about the current strategies being adopted for a safe, effective and specific treatment for toxic metals/ metalloid (lead, arsenic and cadmium).